Subsurface Thermal Modeling of Oxia Planum, Landing Site of ExoMars 2022. (2nd September 2021) - Formisano, M.; De Sanctis, M. C.; Federico, C.; Magni, G.; Altieri, F.; Ammannito, E.; De Angelis, S.; Ferrari, M.; Frigeri, A.
Abstract : Numerical simulations are required to thermophysically characterize Oxia Planum, the landing site of the mission ExoMars 2022. A drilling system is installed on the ExoMars rover, and it will be able to analyze down to 2 meters in the subsurface of Mars. The spectrometer Ma_MISS (Mars Multispectral Imager for Subsurface, Coradini and Da Pieve, 2001) will investigate the lateral wall of the borehole generated by the drill, providing hyperspectral images. It is not fully clear if water ice can be found in the subsurface at Oxia Planum. However, Ma_MISS has the capability to characterize and map the presence of possible ices, in particular water ice. We performed simulations of the subsurface temperatures by varying the thermal inertia, and we quantified the effects of self-heating. Moreover, we quantified the heat released by the drilling operations, by exploring different frictional coefficients and angular drill velocities, in order to evaluate the lifetime of possible water ice.